A retrospective analysis of adverse drug reaction reported in a tertiary care hospital - Saxena, Kirti; Tailor, Chaitali; Mehta, Chaitali; Gajera, Paresh; Srivastava, S. K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The adverse drug reactions (ADRs) reported to pharmacovigilance centre in tertiary care hospital was analysed to find out the incidence and causality. Methods: This was a retrospective study to analyse the ADR reported at pharmacovigilance centre after ethical clearance from Institutional Ethic Committee (IEC). ADR data were analysed and ADRs were categorized as department-wise, system affected and causative drug. The causality of each ADR was assessed by WHO-UMC scale. Results: The majority of patients who had suffered from ADRs were between 19-64 years of age (94.2%) and male patients (58.6%) were affected more than female (41.4%). Pulmonary medicine department has reported highest number of ADR followed by dermatology department. Skin (46.5%) was most affected system followed by gastrointestinal (30.45%), CNS (21.26%), respiratory (9.0%) and remaining systems. Rifampicin (13.79%) shows the largest numbers of ADR followed by zidovudine (13.21%), nevirapine (12.64%) and diclofenac sodium (8.0%). The maximum ADRs reported were probable (94.8%) followed by possible (5.2%). Conclusions: In conclusion, the skin was most affected system followed by gastrointestinal, central nervous and respiratory system. Rifampicin has caused maximum ADRs followed by zidovudine, nevirapine and diclofenac sodium. The causality analyses showed that majority of ADRs were probable (94.8%) while remaining falls in possible (5.2%) category.